The Political Economy of U.S Monetary Policy: How the Federal Reserve Gained Control and Uses It - Dickens, Edwin (Ola Financiera, 2013)
Mainstream economists explain the Federal Reserve’s behavior as (usually failed) attempts to stabilize the economy on a non-inflationary growth path. In contrast, in this paper I explain it in terms of class and intra-class conflicts, with the class conflict taking the form of a populist movement prior to the New Deal then a movement towards social democracy, while the intra-class conflict at issue here is between the large regional banks and the large New York banks. We will see that, when these two groups of banks are united, they constitute an unassailable force in the class conflict. However, when the large regional banks are at loggerheads with the large New York banks, over the proper role of bank clearinghouses during the populist period and the proper role of the Eurodollar market during the social democratic period, then there is an opening for progressive social reforms.